Perspectives on Males and Singing
XX, 368 p.
Keywords: “Since singing is so good a thing,I wish all men would learne to sing” (William Byrd, 1588) Over the centuries, there has been reluctance among boys and men to become involved in some forms of singing. Perspectives on Males and Singing tackles this conundrum head-on as the first academic volume to bring together leading thinkers and practitioners who share their insights on the involvement of males in singing. The authors share research that analyzes the axiomatic male disinclination to sing, and give strategies designed to engage males more successfully in performing vocal music emphasizing the many positive effects it can have on their lives. Inspired by a meeting at the Australian symposium ‘Boys and Voices’, which focused on the engagement of boys in singing, the volume includes contributions from leading authorities in Australia, New Zealand, Canada, the United States and Europe.